The Elizabethan Catholic underground: clandestine printing and scribal subversion in the English counter-reformation - Havens, Earle; Rankin, Mark (Library of the written word, 2025)
"This is the first book-length study dedicated entirely to the clandestine print and scribal culture of members of the international Elizabethan Catholic underground, c. 1558-1603. Close studies offer fresh material textual evidence of a truly cosmopolitan, polyglot, and trans-European community of domestic and exiled English Catholics, moving well beyond the British Isles to the Dutch Low Countries, France, Poland, Spain, and Italy. Explorations of book smuggling networks, clandestine printers, secret Catholic libraries, illicit scribal publications, international patronage and finance, and press censorship combine in this volume to shed new light on an otherwise shadowy, often subversive, but still relatively understudied early modern book culture"--